Penggunaan Arang Aktif Ampas Kopi untuk Menurunkan Bilangan Peroksida dan Asam Lemak Bebas (ALB) pada Minyak Goreng Bekas : Utilization of Activated Charcoal from Coffee Grounds to Reduce Peroxide Number and Free Fatty Acid (FFA) in Used Cooking Oil - Prismawiryanti; Andarwati, Sophia; Syamsuddin (KOVALEN: Jurnal Riset Kimia, 2023)
The peroxide value and free fatty acid content influence the quality of cooking oil. Activated charcoal from coffee grounds has been used in processing used cooking oil. This research aimed to determine the ratio of coffee grounds activated charcoal adsorbent-to-used cooking oil (w/v) and the optimum contact time to reduce used cooking oil's peroxide and free fatty acid levels. The ratio of adsorbent and used cooking oil was 1:20, 1:10, and 1:5 (w/v) with contact times of 60, 90, and 120 minutes. Coffee grounds charcoal was activated by ZnCl2. A ratio of adsorbent and cooking oil 1:5 (10 g activated carbon and 50 ml cooking oil) reduced the peroxide number from 12 mek/O2 kg to 9.8 mek/O2 kg and free fatty acids from 0.972% to 0.383%. A contact time of 120 minutes could optimally reduce the peroxide number and free fatty acids from 12 mek O2/kg to 9.3 mek O2/kg and 0.972% to 0.332%, respectively. Coffee grounds have the potential to be processed into activated charcoal for refining used cooking oil.